Analisis Faktor Produktivitas Kerja Menggunakan Smart PLS pada Industri Konstruksi Baja - Cintha Niszar BungaKusuma; Minto Waluyo (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Changes in work patterns after the COVID-19 pandemic have an impact on CV's daily productivity. Superior Jaya. Companies engaged in steel construction have decreased work productivity which has resulted in a decrease in company performance. This study aims to determine the relationship between work motivation, occupational health and job satisfaction on work productivity and to determine the relationship between work productivity and employee welfare. This research was conducted with a quantitative descriptive approach using Smart Pls software for SEM modeling. The results of this study found that there is a significant influence between occupational health on work productivity and there is a significant influence between work motivation on work productivity. Then there is no effect of job satisfaction on work productivity and work productivity does not have a significant effect on employee welfare. Efforts to increase work productivity can be done by improving the ergonomics of the workspace, striving for a balance between salary and workload, and increasing employee job satisfaction by providing bonuses. This research can provide efforts to improve the work environment to be more productive and also scientific confirmation of the relationship between occupational health, work motivation, and work productivity in the context of the steel construction industry.